Patogenicidade dos fungos Beauveria bassiana (BALS.) VUILL. e Metarhizium anisopliae (METSCH) SOROK em diferentes concentrações sobre Cornitermes cumulans (KOLLAR, 1832) (isoptera: termitidae). - Santos, Priscila Assunção dos (2009)
The entomopathogenic fungi are primarily responsible for the natural mortality of insects in agricultural ecosystems, acting this way in the biological control of pests. The objective of this scientific research experiment was to evaluate the pathogenicity of the fungus Beauveria bassiana (Bals.) isolated URPE 18 and Metarhizium anisopliae (Metsch) Sorok isolated IBCB 42 on the termite mound Cornitermes cumulans. The research experiment was developed in the Laboratory of Entomology and Plant Pathology, Center for Agricultural Biotechnology in a University State of Maranhão. The treatments we used concentrations 1x105 , 1x106 , 1x107 , 1x108 conidia / mL of each of the entomopathogenic fungi and a control (distilled water) with five treatments and six replications in a completely randomized design. In each plastic container (capacity 100 mL) was added 10g of material removed from the mound, a disc of wet cardboard 1.5 cm in diameter and 20 insects, and 4 soldiers and 16 termite workers. The experiment was conducted in a controlled conditions at 25 + 2 ° C, 70 + 10% RH and continuous scotophase. The evaluations were performed daily until the seventh day after inoculation by counting the number of dead termites. The concentration of 1x108 , 1x107 and 1x106 conidia / mL of B. bassiana and M. anisopliae were efficient in controlling C. cumulans. The formation of mycelial B. bassiana was observed between 24 and 48 hours on average after inoculation and M. anisopliae 6 days after inoculation. Fungi M. anisopliae and B. bassiana have potential to be used in a biological control of C. cumulans.